Capillaries in the epithelium of pterygium. Issue 1 (1st January 1998) - Seifert, Peter; Sekundo, Walter
Abstract : AIM: To present new morphological observations of intraepithelial capillaries in pterygium and to provide some explanations for this phenomenon. METHODS: The ultrastructural features of pterygia from 26 patients were examined. Surgically excised tissue was processed for conventional light and transmission electron microscopy. RESULTS: Individual capillaries within the epithelium of the anterior half towards the head of pterygia were identified in 11 specimens out of 26 pterygia examined (42.3%). The perivascular connective tissue of the intraepithelial capillaries contained fibroblasts, collagen fibrils, and elastin-like material. Epithelial cells surrounding these capillaries showed defects in the basal lamina in contrast with the continuous basal lamina of the endothelium. In the intercellular space of the epithelium an amorphous substance, occasional fibroblast processes, and collagen fibrils were frequently observed. CONCLUSION: Capillaries in the epithelium of pterygia are rare, but not exceptional. The ingrowth of these vessels from the stroma into the epithelium can be interpreted as a reaction to hypoxia or deficiency of any other substance transported via the bloodstream. Apparently, the perivascular connective tissue can be used by ingrowing fibroblasts as a migration pathway. The migrating fibroblasts appear to use the defects of the epithelial basal lamina (whether partially or complete) in order to reach the intercellular space. It is possible that collagen fibrils in the epithelial intercellular space have been laid down by fibroblasts which contribute to the pathological dedifferentiation of the conjunctival epithelium.